Phosphate: are we squandering a scarce commodity? - Ferro, Charles J.; Ritz, Eberhard; Townend, Jonathan N. (Nephrology, dialysis, transplantation, 2015)
Abstract. Phosphorus is an essential element for life but is a rare element in the universe. On Earth, it occurs mostly in the form of phosphates that are widespread but predominantly at very low concentration. This relative rarity has resulted in a survival advantage, in evolutionary terms, to organisms that conserve phosphate. When phosphate is made available in excess it becomes a cause for disease, perhaps best recognized as a potential cardiovascular and renal risk factor. As a reaction to the emerging public health issue caused by phosphate additives to food items, there have been calls for a public education programme and regulation to bring about a reduction of phosphate additives to food. During the Paleoproterzoic era, an increase in the bioavailability of phosphate is thought to have contributed significantly to the oxygenation of our atmosphere and a dramatic increase in the evolution of new species. Currently, phosphate is used poorly and often wasted with phosphate fertilizers washing this scarce commodity into water bodies causing eutrophication and algal blooms. Ironically, this is leading to the extinction of hundreds of species. The unchecked exploitation of phosphate rock, which is an increasingly rare natural resource, and our dependence on it for agriculture may lead to a strange situation in which phosphate might become a commodity to be fought over whilst at the same time, health and environmental experts are likely to recommend reductions in its use.